Mário Cesariny, critic artist - Lessa, Maria Silva Prado (eLyra, 2019)
One of the central motives of Mário Cesariny’s poetic is the encounter with different artists’ works – as we can see in his paintings, sculptures, drawings and writings. In the book As Mãos na Água, a Cabeça no Mar [Hands On Water, Head In The Sea], the voice of the poet Cesariny seems to give way to a more open speech by putting before the readers his workroom, presenting the creative process as a learning and an encounter with the other. The plurality of dialogues and the multiplicity of parodies, citations and nominal mentions make the reader dedicated to his work doubt the author's position, seeking in each poem, screen, object and translation what is genuinely from Cesariny and that which comes from another artist. Reading the translated poem “Os passeios” [“The walks”], published in As Mãos na Água [...], the reader attentive to the mixtures of speeches questions himself about the authorship of the text: Kandinsky or Cesariny?